The putting patients first field guide : global lessons in designing and implementing patient-centered care - Frampton, Susan B.; Charmel, Patrick A.; Guastello, Sara (San Francisco : Jossey-Bass, a Wiley Brand, 2013)
"The Putting Patients First Field Guide: Global Lessons in Designing and Implementing Patient Centered Care is the ultimate real-world guide to how hospitals, long-term care communities and integrated health care systems around the world are operationalizing the fundamental dimensions of a patient-centered culture, including access to information, family involvement, healing environments, employee and physician engagement, patient advocacy and more. Edited by Susan Framption and Patrick Charmel of Planetree, a nonprofit consulting and research organization dedicated to patient centered care, the book represents a concrete pathway to patient-centered excellence, using lessons from organizations around the world. By featuring real life examples of providers from nearly every continent, this book will underscore the adaptability of a patient-centered approach to accommodate cultural nuances while addressing the universal desire for patients and family members across cultures for holistic health care experiences that promote humanity, partnership and transparency."--
Contents note continued: ch. Ten Partnering with Patients and Families to Improve Quality and Safety / Anna Lee -- ch. Eleven The Role of Physicians in Patient-Centered Care / Anna W. J. Omtzigt -- ch. Twelve Creating a Patient-Centered Continuum of Care / Heidi Ruis.
Includes bibliographical references and index.
Keywords: Patient-centered health care; Patient-Centered Care -- methods; Physician-Patient Relations; Quality Assurance, Health Care -- methods